What is the optimal age for withdrawing Social Security Benefits? Full Retirement Age, Late Withdrawal Age of 70, or Early Withdrawal Age of 62 - Kohli, Raj K.; Pant, Anurag (Archives of Business Research, 2021)
When to retire is an individual decision based on many criteria like health of the individual, family responsibilities, expected life of the individual, single family income or dual family income, and other such considerations. A financial consideration can also be made. Retiring early will imply a reduction in social security benefits for the rest of your life. Retiring later than your full retirement age can mean a significant bump in benefits for the rest of your life. This paper simulates different conditions to estimate how long a life one needs to live to recover from the reduction in benefits resulting from earlier retirements. Specifically, we model four permutations of the time value of money and the marginal tax rate on early benefits. Our results show there are significant advantages of withdrawing early benefits in most cases where life expectancy is shorter. But when expected life terms are much higher above 83, delaying retirement can significantly enhance the payout of benefits.